Effect of successive cuttings on uptake and partitioning of 15N among plant parts of Leucaena leucocephala - Sanginga, N.; Zapata, F.; Danso, S.K.A.; Bowen, G.D. (Springer, 1990)
We studied the effect of three successive cuttings on N uptake and fixation and N distribution in Leucaena leucocephala. Two isolines, uninoculated or inoculated with three different Rhizobium strains, were grown for 36 weeks and cut every 12 weeks. The soil was labelled with 50 ppm KNO 3 enriched with 10 atom % 15N excess soon after the first cutting. Except for the atom % 15N excess in branches of K28 at the second cutting, both the L. leucocephala isolines showed similar patterns of total N, fixed N2, and N from fertilizer distribution in different parts of the plant at each cutting. The Rhizobium strain did not influence the partitioning of ~SN among the different plant parts. Significant differences in 15N enrichment occurred in different parts. Live nodules of both isolines showed the lowest atom % 15N excess values (0.087), followed by leaves (0.492), branches (0.552), stems (0.591), and roots (0.857). The roots contained about 60~ of the total plant N and about 70~ of the total N derived from fertilizer over the successive cuttings. The total N 2 fixed in the roots was about 60~ of that fixed in the whole plant, while the shoots contained only 20~ of the fixed N2. We conclude that N reserves in roots and nodules constitute another N source that must be taken into account when estimating fixed N 2 or the N balance after pruning or cutting plants. ~SN enrichment declined up to about fivefold in the reference and the N2-fixing plants over 24 weeks following the 15N application. The proportion and the amounts of N derived from fertilizer decreased, while the amount derived from N 2 fixation increased with time although its proportion remained constant.